Chromosomal Differentiation of Deschampsia (Poaceae) Based on Four Satellite DNA Families - González, María Laura; Chiapella, Jorge Oscar; Urdampilleta, Juan Domingo (Frontiers in Genetics, 2021)
Diverse families of satellite DNA (satDNA) were detected in heterochromatin regions of Deschampsia. This kind of repetitive DNA consists of tandem repeat sequences forming big arrays in genomes, and can contribute to lineages differentiation. The differentiation between types of satDNA is related to their sequence identity, the size and number of monomers forming the array, and their chromosomal location. In this work, four families of satDNA (D2, D3, D12, D13), previously isolated by genomic analysis, were studied on chromosomal preparations of 12 species of Deschampsia (D. airiformis, D. antarctica, D. cespitosa, D. cordillerarum, D. elongata, D. kingii, D. laxa, D. mendocina, D. parvula, D. patula, D. venustula and Deschampsia sp) and one of Deyeuxia (D. eminens). Despite the number of satDNA loci showed interspecific variation, the general distribution pattern of each satDNA family is maintaining. The four satDNA families are AT-rich and associated to DAPI+ heterochromatin regions. The D2, D3 and D12 have manly subterminal distribution, while the D13 is distributed in intercalary regions. Such conservation of satDNA pattern suggests a not random distribution in genomes, where the variation between species is mainly associated with the array size and the loci number. The presence of the studied satDNAs in all species highlights the low genetic differentiation between species, in terms of sequences. On the other hand, the variation of the distribution pattern of satDNAs has no clear association with phylogeny. This may be related to high differential amplification and contraction of sequences in different chromosomal positions between lineages, even intraspecifically as was seen for D. antarctica and D. cespitosa. The evolution of these satDNA families in Deschampsia could be explained by the library hypothesis, which proposes that differential amplification of satDNA may be the cause of such differences between species.